The Integrated Space of Conflict Management - GBEHI, CLÉMENT (My University, 2021)
The aim of this article is to examine how conflict management serves to further demand-oriented services. Two observations articulate the reflexions: the reduction of the participation of the State in national economies, and the public support for subsidizing the agricultural sector, and the promotion of demand-oriented approach. As demand-oriented approach involved multiple actors with differences in cultural norms and problem perceptions, conflict management is an integrated space. This article then argues that conflict management involves joint exploration and situation analysis, formulating and achieving action-plans, transferring the collective learning process, and creating context of re-negotiation. The methods on data collection and analysis included semi-structured interviews with key stakeholders and participant observations. The interviews were supplemented with one hundred and eighty individual surveys conducted in a dozen villages. The results prove that demand articulation is comparable to integrated space catalysing conflict management as stakeholders involved have differences in expectations and interests. These inevitably mean that farmers’ demands are diverse. As consequence, some negotiations were made between the competing expectations and demands. The article slights the term “joint construction of demands” to account for the agreements and disagreements that shape, in part, what is feasible in a given context.
Keywords: Meeting Farmers’ Demands; Integrated Space; Conflict; management; Knowledge-Based Services; Benin